HLA antigens in acute anterior uveitis in South African blacks. Issue 5 (May 1980) - Maier, G; Miller, B; Freedman, J; Baumgarten, I
Abstract : Fifty-three black patients with acute nongranulomatous anterior uveitis (AAU) were tissue typed and the results compared to those from a panel of 200 healthy unrelated black volunteers. No statistically significant deviation from the norm with regard to the frequencies of 38 HLA antigens could be observed.